Screening of potential food grade pigment-producing microbes from New Zealand environment - Kamarudin, Kamarul Rahim; K., Robert; Lewis, G. D.; Greenwood, David R.; Villas-Bôas, Silas (2008)
Stronger interest in natural food colorants as alternatives to synthetic colorants has greatly aroused among the modern consumers due to food safety and health concerns. The reduced number of permitted synthetic food colorants from 80 to 16 compounds resulted from studies started in 1904 has attracted manufacturers to focus more on production of natural food colorants from plants. However, since the production costs for plant-derived food colorants are comparatively ineffective and not competitive, the new focuses are to assess more potential food grade pigment-producing microbes and improve their production yields for large-scale industrial application. Accordingly, this study aims to find new and cheaper sources of natural food grade pigments from New Zealand environmental-isolated microbes. The screening of selected pigment-producing microbes from the School of Biological Sciences (SBS) culture collection to date indicates a number of potential natural pigments with various colour-shades successfully extracted using methanol. There are also a few water-soluble pigments excreted into the culture medium. Commercial saffron (Crocus sativus) crude extract was used as a standard water-soluble natural pigment to establish a High Performance Liquid Chromatography (HPLC) method for pigment separation and purification. Pigments from 60 different microbial strains have been extracted and their HPLC purification is being carried out in order to have their physical chemical properties assayed.